Hepatic Tuberculous Abscess with Extension into Anterior Abdominal Wall - Sanjay M Khaladkar; Radhika K Jaipuria; Ronak Savani; Shibani Saluja (Journal of Clinical and Diagnostic Research, 2019)
Hepatic Tuberculosis (TB) is rare form of extrapulmonary TB. Prevalence of primary tubercular abscess is 0.34% in hepatic TB. Isolated hepatic TB is rare with few reported sporadic cases. Primary hepatic tubercular abscesses rupturing into anterior abdominal wall is rare. The skeletal muscles are uncommonly affected by TB and are less preferred site for multiplication and survival of Mycobacterium tuberculosis due to abundant blood supply, lack of lymphatic and reticulo-endothelial tissue in muscles and high lactic acid content. We report a case of 36-year-old patient who presented with lump in anterior abdominal wall in right hypochondriac region since one month. On ultrasound and CT study, he was detected to have hepatic abscess in right lobe with extension to overlying anterior abdominal wall. TB-PCR showed Mycobacterium complex. Genprobe test was positive for Mycobacterium tuberculosis complex. Patient improved after Antikoch’s Treatment (AKT) with regression in hepatic and abdominal wall abscesses.